Exon deletions and intragenic insertions are not rare in ataxia with oculomotor apraxia 2 - Kreuz Friedmar; Bürk Katrin; Minnerop Martina; Bernard Veronica; Gillessen-Kaesbach Gabriele; Zühlke Christine (BMC, 2009)
Abstract Background The autosomal recessively inherited ataxia with oculomotor apraxia 2 (AOA2) is a neurodegenerative disorder characterized by juvenile or adolescent age of onset, gait ataxia, cerebellar atrophy, axonal sensorimotor neuropathy, oculomotor apraxia, and elevated serum AFP levels. AOA2 is caused by mutations within the senataxin gene (SETX). The majority of known mutations are nonsense, missense, and splice site mutations, as well as small deletions and insertions. Methods To detect mutations in patients showing a clinical phenotype consistent with AOA2, the coding region including splice sites of the SETX gene was sequenced and dosage analyses for all exons were performed on genomic DNA. The sequence of cDNA fragments of alternative transcripts isolated after RT-PCR was determined. Results Sequence analyses of the SETX gene in four patients revealed a heterozygous nonsense mutation or a 4 bp deletion in three cases. In another patient, PCR amplification of exon 11 to 15 dropped out. Dosage analyses and breakpoint localisation yielded a 1.3 kb LINE1 insertion in exon 12 (patient P1) and a 6.1 kb deletion between intron 11 and intron 14 (patient P2) in addition to the heterozygous nonsense mutation R1606X. Patient P3 was compound heterozygous for a 4 bp deletion in exon 10 and a 20.7 kb deletion between intron 10 and 15. This deletion was present in a homozygous state in patient P4. Conclusion Our findings indicate that gross mutations seem to be a frequent cause of AOA2 and reveal the importance of additional copy number analysis for routine diagnostics.